(untitled) (Castilla. Estudios de Literatura, 2018)
The purpose of this article is to defend the idea that the way in which Jorge Guillen reacts to the works of others is in a critical, creative and dialogic way. Guillén’s Homenaje is a book full with multiple literary references many of which trace his literary preferences. We will examine his approach to a specific Spanish baroque poem: Epístola Moral a Fabio. The contemporary poet will dispute many of the philosophical and ethical precepts contained in Fernández de Andrada’s seminal poem and by doing so the will create some of the most interesting compositions of Homenaje. We will consider additional poems belonging to his Aire nuestro, poems that also reflect on the very same critical tradition.